Interplay of structural and compositional effects on carrier recombination in mixed-halide perovskites. Issue 90 (12th September 2016) - Talbert, Eric M.; Zarick, Holly F.; Orfield, Noah J.; Li, Wei; Erwin, William R.; DeBra, Zachary R.; Reid, Kemar R.; McDonald, Christopher P.; McBride, James R.; Valentine, Jason; Rosenthal, Sandra J.; Bardhan, Rizia
Abstract : We investigate the effect of grain structure and bromide content on charge transport in methylammonium lead iodide/bromide perovskites by probing the steady-state and time-resolved photoluminescence of planar films with distinct morphologies. Abstract : In this work, we investigate the effects of grain structure and bromide content on charge transport in methylammonium lead iodide/bromide (MAPb(I1− x Br x )3 ) perovskites by examining the steady-state (ss-PL) and time-resolved (tr-PL) photoluminescence of planar films with varying grain size and bromide content. We controlled the perovskite grain structure via solvent engineering with N, N -dimethylformamide (DMF) or dimethyl sulfoxide : γ-butyrolactone (DMSO : GBL), and the resultant grain morphology was independent of Br doping between 0–33%. Carrier lifetimes ranged from 29–52 ns with increasing Br content for DMF-produced perovskite films, and from 2–9 ns for films obtained with DMSO : GBL. Analysis of XRD and photoluminescence data suggests this order-of-magnitude difference in lifetimes is attributable to the nature of iodide-rich recombination nuclei within the bulk perovskite. By modulating the precursor solvent and Br composition, the influence of low-bandgap recombination nuclei can be minimized to enhance charge transport and lengthen the carrier lifetime in mixed-halide perovskite films.